Spectrum of chest computed tomographic (CT) findings in coronavirus disease-19 (COVID-19) patients in India. Issue 129 (August 2020) - Parry, Arshed Hussain; Wani, Abdul Haseeb; Yaseen, Mudasira; Dar, Khurshid Ahmad; Choh, Naseer Ahmad; Khan, Naseer Ahmad; Shah, Naveed Nazir; Jehangir, Majid
Highlights: Two-thirds of the laboratory-confirmed SARS-CoV-2 patients had a normal chest CT. One-third patients with chest CT findings presented a typical pattern of GGOs in peripheral and posterior distribution. Small pulmonary vessel enlargement seems to be a unique feature of COVID-19 pneumonia with a diagnostic value. Abstract: Purpose: To report the spectrum of chest computed tomographic (CT) imaging findings in coronavirus disease-19 (COVID-19) infected Indian patients. Methods: This was a prospective descriptive study comprising 147 consecutive reverse transcriptase polymerase chain reaction (RT-PCR) positive patients who underwent CT chest. Prevalence, distribution, extent and type of abnormal lung findings were recorded. Results: Among the total study cohort of 147 patients, 104 (70.7 %) were males and 43 (29.3 %) were females with mean age of 40.9 ± 17.2 years (range 24–71 years). We observed lung parenchymal abnormalities in 51 (34.7 %) cases whereas 96 (65.3 %) RT-PCR positive cases had a normal chest CT. Only 12.2 % of the patients were dyspneic, 6.1 % had desaturation, 7.4 % had increased respiratory rate and 10.9 % had comorbidities. Among the patients with abnormal CT findings bilateral 39/51 (76.5 %), multilobar (88.2 %) lung involvement with a predominant peripheral and posterior distribution was commonly observed. With regards to the type of opacity, ground glass opacity (GGO) was the dominant abnormality found in all 51 (100 %) cases. Pure GGO was observed in 15 (29.4 %), GGO with crazy paving pattern was seen in 15 (29.4 %) and GGO mixed with consolidation was noted in 21(41.2 %). Peri-lesional or intralesional segmental or subsegmental pulmonary vessel enlargement was observed in 36 (70.6 %) cases. Conclusion: In this study population predominantly with mild symptoms and few comorbidities, two-thirds of RT-PCR positive patients had a normal chest CT; whereas the remaining patients showed typical findings of predominant GGOs with a bilateral distribution and peripheral predominance.